2022
DOI: 10.1038/s41467-022-28913-5
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum reduces METTL3-mediated m6A modification and contributes to colorectal cancer metastasis

Abstract: Microbiota-host interactions play critical roles in colorectal cancer (CRC) progression, however, the underlying mechanisms remain elusive. Here, we uncover that Fusobacterium nucleatum (F. nucleatum) induces a dramatic decline of m6A modifications in CRC cells and patient-derived xenograft (PDX) tissues by downregulation of an m6A methyltransferase METTL3, contributing to inducation of CRC aggressiveness. Mechanistically, we characterized forkhead box D3 (FOXD3) as a transcription factor for METTL3. F. nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 45 publications
1
82
0
1
Order By: Relevance
“…F. nucleatum abundance correlates with high glucose metabolism in CRC patients, and F. nucleatum targetes lncRNA ENO1-IT1 promotes CRC glycolysis and tumor progression (94). F. nucleatum induced a dramatic decrease in m 6 A modification in CRC cells and patient-derived xenograft tissues through downregulation of the m 6 A methyltransferase METTL3, resulting in CRC aggressiveness (95). A study quantified F. nucleatum DNA in 181 colorectal cancer liver metastasis (CRLM) specimens and found that F. nucleatumpositive CRLM showed a significantly lower density of CD8 + T cells and a higher density of MDSCs compared to F. nucleatumnegative CRLM, and the difference was statistically significant, but the relationship between F. nucleatum and density of tumorassociated macrophages (TAMs) was not statistically significant (96).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…F. nucleatum abundance correlates with high glucose metabolism in CRC patients, and F. nucleatum targetes lncRNA ENO1-IT1 promotes CRC glycolysis and tumor progression (94). F. nucleatum induced a dramatic decrease in m 6 A modification in CRC cells and patient-derived xenograft tissues through downregulation of the m 6 A methyltransferase METTL3, resulting in CRC aggressiveness (95). A study quantified F. nucleatum DNA in 181 colorectal cancer liver metastasis (CRLM) specimens and found that F. nucleatumpositive CRLM showed a significantly lower density of CD8 + T cells and a higher density of MDSCs compared to F. nucleatumnegative CRLM, and the difference was statistically significant, but the relationship between F. nucleatum and density of tumorassociated macrophages (TAMs) was not statistically significant (96).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…A study also finds that FadA promotes SW480 cell growth and proliferation in a dose and time-dependent manner [ 19 ]. In addition, Fn-induced miR-4717 promotes CRC cell line proliferation via METTL3-dependent m6A modification [ 20 , 21 , 22 ]. Lee et al [ 23 ] suggested that Fn might be linked to promoting CRC cell growth, invasion, and pro-tumoral immune responses in MSI-high CRCs.…”
Section: Potential Mechanisms By Which Fn May Promote Crc Proliferati...mentioning
confidence: 99%
“…FOXD3 is a transcription factor for METTL3, an m6A methyltransferase, and there is evidence that Fn could diminish the expression of FOXD3 and suppress the transcription of METTL3 via YAP pathway activation. Its target, KIF26B, is promoted by the decline in m6A modifications and mRNA degradation, which are responsible for Fn-related CRC metastasis [ 22 ].…”
Section: Potential Mechanisms By Which Fn May Promote Crc Proliferati...mentioning
confidence: 99%
“…RNA modification is one of the common mechanisms by which environmental stimuli influence cellular functions 4,[19][20][21][22] . We found that BHPF induced tissue-specific ferroptosis and apoptosis in an m 6 A dependent manner, leading to cardiac and vascular developmental defects, respectively.…”
Section: Main Textmentioning
confidence: 99%